Environmental Metals and Cardiovascular Disease in Adults: A Systematic Review beyond Lead and Cadmium - Nigra, Anne E (Curr Environ Health Rep, 2016)
Published systematic reviews concluded that there is moderate to strong evidence to infer a potential role of lead and cadmium, widespread metal exposures, as cardiovascular risk factors. For other non-essential metals, the evidence has not been appraised systematically. Our objective was to systematically review epidemiologic studies on the association between cardiovascular disease in adults and the environmental metals antimony, barium, chromium, nickel, tungsten, uranium, and vanadium. We identified a total of 4 articles on antimony, 1 on barium, 5 on chromium, 1 on nickel, 4 on tungsten, 1 on uranium and 0 on vanadium. We concluded that the current evidence is not sufficient to inform on the cardiovascular role of these metals because the small number of studies. Few experimental studies have also evaluated the role of these metals in cardiovascular outcomes. Additional epidemiologic and experimental studies, including prospective cohort studies, are needed to understand the role of metals, including exposure to metal mixtures, in cardiovascular disease development.